A pilot study for sustainable ecotourism at Gunong Stong State Park, Kelantan using Visitor Experience and Resource Protection (VERP) management framework - Hassin, Nor Hizami; Muhamad Noor, Amal Najihah; Mungkar, Andi Nazihah; Hasnil, Hafira Ulfah; Abdul Rahman, Nur Hidayah; Abas, Muhamad Azahar; Abdul Karim, Muhammad Firdaus (UMK Press, 2019)
Ecotourism plays a vital role in tourism industries and has become one of the effective practices towards conservation effort in the natural environment activity. Thus, it is important to know the concept of carrying capacity issues applied to the area pertaining to the visitors’ experiences, to ensure the benefits it brings to the socio-cultural, economic, and environmental sustainability of the area. The objective of this study was to identify the relationship of visitors’ experience and the protection of the natural resources at Gunung Stong State Park (GSSP) using the management framework of Visitor Experience and Resource Protection (VERP). This approach provided a set of management framework in order to manage the sustainable ecotourism in GSSP without abandoning the good manner of visitor experiences. A total of 35 respondents have participated in this pilot study and our result showed that the tourists’ satisfaction towards the GSSP was at moderate level. Therefore, the GSSP was suitable for nature tourism attraction. However, a proper management of the park is required whilst the biodiversity there is still intact. The management of GSSP can be further improved by instilling awareness among visitors in order to sustain the ecotourism activity, and attract more tourists besides improving their experience throughout their visit.